1996
DOI: 10.1111/j.1365-2575.1996.tb00008.x
|View full text |Cite
|
Sign up to set email alerts
|

A framework for linking Soft Systems Methodology (SSM) and Jackson System Development (JSD)

Abstract: This paper describes a proposed framework for linking soft systems methodology (SSM), a problem structuring technique for use in messy, ill-defined problem situations, with Jackson System Development (JSD), an information system development methodology which has object-oriented characteristics. The approach taken has been to embed the modelling phase of JSD within SSM after the conceptual modelling stage, but before the debate on desirable and feasible change. The JSD modelling phase is carried out at a concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…One of the fundamental challenges of undertaking IS design is the need to find some means of moving from methods of inquiry suited to sense making in social situations, to methods suited to organizing knowledge into a suitable format for the construction of a logical specification for any supporting technology. Many authors have discussed the suitability of using Soft Systems Methodology (SSM) (Checkland, 1981;Scholes, 1990, 1999) to support initial sense making in a problem of concern, but problems have been encountered in linking up with methods for constructing technological specifications (Doyle, Wood, and Wood-Harper, 1993;Lai, 2000;Liang, West, and Stowell, 1998;Mathiassen and Nielsen, 2000;Miles, 1988;Prior, 1992;Savage and Mingers, 1996;Stowell and West, 1994). Most approaches to creating such a link have attempted to create some sort of bridge between the first phase of inquiry, exploration and sense making and the second phase, constructing a logical specification.…”
Section: Introductionmentioning
confidence: 99%
“…One of the fundamental challenges of undertaking IS design is the need to find some means of moving from methods of inquiry suited to sense making in social situations, to methods suited to organizing knowledge into a suitable format for the construction of a logical specification for any supporting technology. Many authors have discussed the suitability of using Soft Systems Methodology (SSM) (Checkland, 1981;Scholes, 1990, 1999) to support initial sense making in a problem of concern, but problems have been encountered in linking up with methods for constructing technological specifications (Doyle, Wood, and Wood-Harper, 1993;Lai, 2000;Liang, West, and Stowell, 1998;Mathiassen and Nielsen, 2000;Miles, 1988;Prior, 1992;Savage and Mingers, 1996;Stowell and West, 1994). Most approaches to creating such a link have attempted to create some sort of bridge between the first phase of inquiry, exploration and sense making and the second phase, constructing a logical specification.…”
Section: Introductionmentioning
confidence: 99%
“…These models emphasize the organization of the data and messages that must be passed in order for the real world technological provision to function correctly. In the process of changing the emphasis from thinking about the action to be undertaken within the situation to a focus on creating a technical definition it is difficult to maintain a direct link between the two modelling approaches (Doyle and Wood, 1991;Stowell and West, 1994;Savage and Mingers, 1996). In order to enable clients to take ownership of the proposed change, there is a need for new modelling methods for supporting their complete participation (Stowell, 2000).…”
Section: A Systemic Process Of Inquirymentioning
confidence: 99%
“…Others may be almost entirely excluded, particularly if methods requiring specific technical expertise are employed. For example, in an attempt to link SSM to Jackson's (1983) systems development, Savage and Mingers (1996) argued that the complexity of the notation might exclude some clients from participating in that phase of the design process. The manner in which people were engaged in the learning process is then a matter to reflect upon as fully as possible.…”
Section: Engagement In the Learning Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Mingers (1988), in reply, acknowledged some similarities but indicated that there were fundamental philosophical differences between them; Avison et al (1998) also point out the philosophical difference and conclude that they are not similar. Other proposals include linking "SSM" to the Jackson System Development method (Savage and Mingers, 1996;Wood and Doyle, 1989) and re-expressing a model in a form that can be expressed in propositional calculus and predicate logic in order to derive a type of DFD (Gregory, 1993a-c;Merali, 1992).…”
Section: Adaptationsmentioning
confidence: 99%